2015
DOI: 10.3329/nimcj.v7i1.25704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary tract infection, its causative agents and antibiotic sensitivity pattern : A study in Northern International Medical College Hospital, Dhaka

Abstract: Background : Urinary tract infection (UTI) is one of the most important causes of morbidity and mortality in the developing countries like Bangladesh. Antimicrobial agents are the frequently used drug for its treatment. Periodic evaluation of antimicrobial activity of different antibiotics is essential as the pattern of antibiotic sensitivity may vary over periods. Increasing antibiotic resistance among urinary pathogens to commonly prescribed drugs has become a global reality today.Objective : To determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
7
16
3
Order By: Relevance
“…Our study showed Ciprofloxacin resistant was 39.45%. Other studies from Bangladesh has been reported similar resistance pattern to ciprofloxacin 29,30 In this study Cefuroxime exhibited poorer activity (42.20%) toward the uropathogens. These data are different from previous study done in BSMMU 14 .…”
Section: Resultsmentioning
confidence: 57%
“…Our study showed Ciprofloxacin resistant was 39.45%. Other studies from Bangladesh has been reported similar resistance pattern to ciprofloxacin 29,30 In this study Cefuroxime exhibited poorer activity (42.20%) toward the uropathogens. These data are different from previous study done in BSMMU 14 .…”
Section: Resultsmentioning
confidence: 57%
“…Out of total patients attending outdoor and indoor departments of VPIMS with symptoms suggestive of UTI, 16.9% had culture positivity, which is close to other studies too. A study in 2011 recorded positivity of 24% 13 and another study by BHN Yasmeen et al 14 in 2014 in Bangladesh showed 21% positivity in urine samples for pathogenic organisms. Similarity in positivity suggests that pathogenecity of resistant isolates is not affected; probably only the clearance of bacteria from host body is delayed.…”
Section: Discussionmentioning
confidence: 95%
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%